Numerical investigation of forced convection heat transfer and flow irreversibility in a novel heatsink with helical microchannels working with biologically synthesized water-silver nano-fluid. (November 2019) - Shahsavar, Amin; Baseri, Mohammad Mehdi; Al-Rashed, Abdullah A.A.A.; Afrand, Masoud
Abstract: This paper aims to evaluate the hydrothermal and irreversibility behaviour of a biological water-Ag nano-fluid in a new heatsink with helical microchannels. Two-phase mixture model is applied to precisely simulate the behavior of nanofluid in the nanoadditive concentration ( φ ) range of 0–1% and Reynolds number ( Re ) range of 500–1500. The influences of φ and Re on the convective heat transfer coefficient, CPU surface temperature, pumping power, as well as the irreversibilities due to heat transfer and fluid friction are examined. The findings depict that boosting the Re and φ augments the performance of heatsink by intensifying the convective heat transfer coefficient of the working fluid which favourably declines the CPU surface temperature and the heat transfer irreversibility and importantly results in the temperature uniformity of the CPU surface. However, intensification in Re adversely affects the pumping power, the fluid friction and total irreversibilities in the system. Furthermore, it is revealed that the nano-fluid always has a superior cooling performance as compared with the pure water. Finally, it is found that the best hydrothermal performance of the nano-fluid in the proposed heatsink occurs at Re = 1500 and φ = 1%, while the minimum total irreversibility occurs at Re = 500 and φ = 1%.